Peran Akuntansi Lingkungan Hidup di Indonesia - Yulianto (LPPM POLITEKNIK LP3I BANDUNG, 2019)
Environmental accounting is the branch of accounting science which records, measures, reports, discloses quantitative data related to problems or issues of environment on stakeholders and entities behalf in order the gradation of environmental quality can be reduced based on financial accounting standard. The object of environmental accounting is externality or external cost. Environmental quality costs can be classified into four categories : (1). prevention costs; (2). detection costs; (3). internal failure costs; and (4). external failure costs. Prevention costs refer to the costs incurred to prevent, or the costs arising as a result of low-quality of the environment. Detection costs refer to the costs intended to determine that product, process, and other activities conform to environmental standards. Internal failure costs refer to the costs incurred on production. External failure costs refer to the costs incurred after production. External cost can be recorded as direct cleaning cost, disposal cost, administrative and legal cost, new plant and equipment cost. The claims of the court can be recorded as contingent liability and must be disclosed on notes to financial statements. There are several methods can be used to measure external cost such as opportunity cost approach, surrogate valuation, interview, survey, questionnaire that involves the victims of negative effects of industrialization or environment as the respondents. The role of environmental accounting in Indonesia is to prepare qualitative data to record, measure, report and disclose transactions and events related to environmental problems in frame of reducing the gradation of environmental quality on firms and stakeholders behalf based on Indonesian financial accounting standard (SAK) and Indonesian constitution and legislation of environment